Development and Implementation of Digital Learning in the Drama Studies Course Based on Local Wisdom - Eti Sunarsih; Zulfahita Zulfahita; Wahyuni Oktavia; Safrihady Safrihady; Lili Yanti; Sri Mulyani; Gunta Wirawan (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Drama Studies learning in higher education often faces challenges of low student engagement due to conventional teaching methods, limited interactivity, and the lack of integration of local cultural values into the learning process. This study aims to develop and implement a digital Project-Based Learning (PBL) model that integrates local wisdom into Drama Studies courses and to disseminate its impact on student learning outcomes. The research employs a developmental research design with a descriptive-qualitative approach, following the 4D model (Define, Design, Develop, and Disseminate). Data were collected through in-depth interviews, classroom observations, documentation of student drama projects, and assessments of cognitive, affective, and psychomotor domains. The results indicate that the developed learning model enhances students’ understanding of drama theory, strengthens their appreciation of local culture, and improves their dramatic performance skills through collaborative projects. The integration of local culture–based digital media also enriches the learning context and significantly boosts student engagement. This study provides a theoretical contribution to the development of a locality-based TPACK framework and offers a practical model applicable to arts education in the digital era. The findings conclude that the collaboration between technology, pedagogical projects, and local culture effectively creates contextual, interactive, and meaningful learning experiences in Drama Studies within higher education.